Soil fertility and poverty - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
Dare to Share! ISBN 3-8236-1273-5, 140 pp. US $25. Margraf Verlag, Postfach 105, 97985 Weikersheim, Germany. Fax: +49 7934 81 56.